Official and unofficial school inspection as hegemonic and counter-hegemonic struggle in Prairie districts before 1940 - Mahe, Yvette T.M (Canadian ethnic studies, 2001)
Francophones assumed that French-speaking Catholic inspectors would be supportive of their cultural needs and aspirations. Over the years, Francophones met with provincial Ministers of Education to request the nomination of French-speaking inspectors (Burelle, 1984; Denis & Li, 1987; Huel, 1969, p. 12, 22-23, 63; La Survivance, 1934a; Le Courrier de l'Ouest, 1912b). Various sources indicate that approximately eleven French-speaking Catholic inspectors were appointed in Prairie provinces between 1897 and 1940; five in Manitoba,(4) three in Saskatchewan,(5) and three in Alberta.(6) It is interesting that all eleven French-speaking inspectors were assigned regular inspection posts. Our data suggests, however, that all three inspectors in Saskatchewan and Inspector Brasset in Alberta never inspected bilingual schools, and that the seven remaining inspectors occasionally visited only those bilingual schools located within their regular inspectorial boundaries (Burelle, 1984; Huel, 1983b; Lapointe & Tessier, 1986, p. 220; Leblanc, 1975). In Manitoba, a former teacher advised Hebert (1997) that when the visiteur inspected her school, he was preoccupied with the implementation of l'Association des educateurs catholiques francais du Manitoba's French Program of Studies, and in evaluating students' progress in French. The visiteur also tried to convince less enthusiastic teachers and trustees of the importance of teaching French and transmitting a French-Canadian world-view for cultural survival, "...et de stimuler les institutrices et les commissaires moins enthousiastes..." (1997, p. 68). Because visiteurs had no legal authority to reprimand teachers who neglected French or religious instruction, they had to negotiate the teachers' role in cultural survival with them. To assist teachers in giving legitimacy to certain forms of cognitive and cultural knowledge, they provided them with pedagogical tools. Mahe (2000), who analyzed 390 inspection reports completed by Father Fortier when he inspected bilingual schools in Alberta between 1934 and 1940, found that during his visits he gave teachers a copy of the Association's French Program of Studies. He also distributed a copy of various French books to assist in the teaching of Grammar, Composition, French Canadian History, and Catechism, and provided children's' story books published by la Societe St-Jean Baptiste as well as Holy History (Histoires Sainte) storybooks and religious pictures. These books, published in Quebec, contained a French-Canadian nationalist, clerical bias. At that time, the only texts prescribed by the Department of Education for teaching French in Alberta were language arts books published in France. All other school subjects had to be taught in English with the English textbooks prescribed by the Department. These texts contained a bias which conformed to the dominant ideology (Mahe, 1993). Mahe (2000) also noted in these reports that Fortier suggested strategies to assist teachers in teaching reading and writing in French, and suggested activities to help them inculcate religious, nationalistic, and patriotic sentiments in students. Osborne (2000) reminds us that schooling was never a simple, top-down imposition of social control owing to the resistance of those who turned it to their own advantage (p. 9). When the state failed to acknowledge their diversity and their historical right to have their children educated in French, Francophones organized power blocks in the form of associations to create a counter-hegemonic curriculum for dissemination in bilingual schools. What became apparent, however, when analyzing data on official and unofficial school inspection was that, in addition to wanting teachers to transmit the French language and culture in bilingual schools, Francophones also expected their children to learn English for economic and social reasons (La Survivance, 1935). Fathers Auclair, Boileau, and Fortier were aware of this phenomenon when they inspected bilingual schools, and they were concerned that English was rapidly becoming the young Francophones' primary language (Auclair, 1927; La Survivance, 1934b; Tessier, 1983). Their observations suggest that cultural transformations emerged out of hegemonic and counter-hegemonic struggles in bilingual school districts. Based on Gramsci's writings, Mouffe (1979) explains that the relations of forces between two rival hegemonic groups who confront each other can result in a perpetual process of transformation (pp. 183-195), and that these processes can take the form of continuous absorption, a passive consensus, or the sifting through past conceptions "to see which ones, with some changes of content, can serve to express the new situation" (p. 192).